PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS IV SD NEGERI 11 PALEMBANG - Ella Febriani; Yasir Arafat; Henni Riyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using audio-visual media on the learning outcomes of fourth-grade students of SDN 11 Palembang. The method used is quantitative with a quasi-experimental design, namely pretest-posttest control group design. The subjects of the study consisted of two classes, namely class IV.C as the control group and class IV.A as the experimental group. The results of the descriptive analysis showed that the average pretest and posttest scores in the control class were 53 and 75.50, respectively, while in the experimental class it increased from 52.86 to 86.67. The t-test produced a t-value of 2.688, which is greater than the t-table of 2.022, indicating that there is a significant effect of using audio-visual media on learning outcomes of Indonesian. Thus, audio-visual media is proven to be effective in improving student learning outcomes.